Pengaruh Kompetensi, Disiplin Dan Motivasi Terhadap Kinerja Karyawan (Studi Kasus Pada CV. Vin_Case) - Teguh Ariefiantoro; Dewi Sania; Asih Niati; Susanto Susanto (Jurnal Bintang Manajemen, 2023)
This study aims to determine the Effect of Competence, Discipline, and Work Motivation on Employee Performance (Case Study at CV. Vin_Case). The population used in this study were all employees of CV. Vin_Case totaling 45 employees. This study uses a quantitative method using a questionnaire. The method of data analysis in this study uses multiple linear analysis with the dependent variable being Employee Performance, while the independent variables are Competence, Discipline and Motivation. In this study using saturated sampling techniques, namely sampling techniques where all members of the population are used as samples. Then the data collection method was through questionnaires and data analysis using SPSS version 21. Data analysis techniques used in this study included validity testing, reliability testing, classical assumption testing, multiple regression analysis, hypothesis testing using the t test and the coefficient of determination test (R2). The results of this study indicate that the independent variables, namely Competence (X1), Discipline (X2) and Motivation (X3) have a positive and significant effect on Employee Performance (Y). Based on the coefficient of determination 58.6 percent of employee performance can be explained by independent variables in this study, while the remaining 41.4 percent is explained by variables not observed in this study.